Evaluation of Hemopoietic Disorders and Renal Function in Children with Chronic Glomerulonephritis Depending on Allelic Gene Polymorphism of IL-10 and IL-1β - V.M. Dudnyk; G.Yu. Zvenigorodska (Zaslavsky O.Yu., 2012)
We have examined 20 children suffering from chronic glomerulonephritis with torpid course of disease and persistent urinary syndrome. It was defined that in children with torpid course of disease genotype C/T gene IL-1β (-511) (p < 0.05) was significantly more common. Also, we found the relationship between allelic variants of cytokines genes and parameters of GFR and endogenous erythropoietin. In children with genotype C/T IL-1β (-511) has been a significant reduction of erythropoietin even in the absence of anemia and iron deficiency (p < 0.05). In identifying the genotype G/G IL-10 (-1082) and C/T, C/C genotype of IL-1β (-511) 1.2-fold lower GFR was observed (p < 0.05).